Submicrometer aerosols and excess CO as tracers for biomass burning air mass transport over southern Africa. Issue 17 (15th September 2016) - Mafusire, Getrude; Annegarn, Harold John; Vakkari, Ville; Beukes, Johan Paul; Josipovic, Miroslav; van Zyl, Pieter Gideon; Laakso, Lauri
Abstract: This paper links surface measurements of biomass burning aerosols and trace gases with trajectory analysis to determine transport pathways for air masses with high and low concentrations. We interpret the long‐term atmospheric monitoring record from a remote monitoring station in central southern Africa (North West Province, South Africa). Trace gas analyzers and a Differential Mobility Particle Sizer were used to measure ground level trace gas and submicron aerosol concentrations. Fire signatures were identified based on excess CO above average tropospheric levels, and episodes of enhanced particulate matter concentrations in the 10 to 840 nm size range. Thirty‐six biomass burning plumes were reported; 7 had strong signals of excess CO, with ratios between 0.41 and 0.64, while 29 had weak signals ranging between 0.07 and 0.32. Pathways identified for the long‐range transport of biomass burning aerosols were as follows: easterly (39% frequency), southwesterly (31%), recirculation (22%), and northerly (8%) flow patterns. CO and Aitken‐mode aerosol number strengths were larger for fire emissions arriving in the easterly and southwesterly air masses than for recirculation and northerly air masses. Easterly and southwesterly flows were dominated by Aitken‐mode aerosol, whereas accumulation‐mode particles dominated in the recirculation and northerly flows. Findings identify biomass burning as a major source of Aitken‐mode aerosols. Enhanced CO concentrations, combined with Aitken‐ and accumulation‐mode particle number size distributions, are shown to provide a useful signature of plumes originating over regional biomass combustion events. Key Points: Combined particle size distributions, CO, and particle number concentration time plots can be used to identify wildfire plumes Frequency of wildfire aerosol episodes at Botsalano was relatively infrequent Results justify the selection of Botsalano as a clean, remote continental location